A multicomponent intervention to reduce internalized stigma in persons with a diagnosis of severe mental disorder: protocol of a pilot randomized mixed trial - Fernández, Dany; Grandón, Pamela; Bustos, Claudio (International Journal of Clinical Trials, 2023)
Background: People with mental disorders face stigma as a social obstacle in multiple areas of their lives. Therefore, stigma toward this population is a priority for global public health due to its numerous consequences for those affected. One of its manifestations is internalized stigma, which also has severe implications for people with mental disorders. This study presents the protocol of a multicomponent intervention aimed at reducing internalized stigma in people with severe mental disorders. Methods: The intervention is based on a mixed-method experimental design. The main design is an external randomized pilot trial with two arms, parallel, double-blind, equally randomized, and single-center. Qualitative data before and after the completion of the intervention are included as a secondary component of the main design. The study will be carried out in health service of the secondary level of care in Gran Concepción, Biobío Region, Chile. Twelve people will participate in the qualitative pre-intervention stage and 34 in the intervention stage, 17 in the experimental group, and 17 in the control group. The experimental group will receive the intervention plus the usual treatment, and the control group will only receive the usual treatment. The intervention is carried out in 10 sessions lasting 90 minutes each and is administered by a health service professional. Conclusions: The study will provide evidence on the acceptability and feasibility of the intervention in the Chilean context, advancing knowledge and understanding in the field. Trial Registration: The study has been registered with trial registration no. ACTRN12622000919718.